Development and Performance Evaluation of a Bevameter for Measuring Soil Strength - Ji-Tae Kim; Dong-U Im; Hyuek-Jin Choi; Jae-Won Oh; Young-Jun Park (Sensors, 2021)
The driving performance of an off-road vehicle is closely related to soil strength. A bevameter is used to measure the soil strength, and it usually consists of two independent devices: a pressure–sinkage test device and a shear test device. However, its development and measurement processes have not been standardized; thus, researchers apply it in various fields according to their own discretion. In this study, a new bevameter was developed, and experiments were conducted to clarify the factors that affect the measurement performance of the bevameter. The pressure–sinkage test device was tested with circular plates of different sizes, and the results confirmed that the pressure–sinkage parameters decreased with the plate size. For the shear-test device, normal pressure was applied using a dead load to prevent normal-pressure variation due to displacement and speed. In addition, a spline was installed on top of the shaft connected to the shear ring to measure slip sinkage during the shear test. The results showed that the slip sinkage increased in proportion to the normal pressure and slip displacement, but the increase gradually decreased and converged to a certain point.